2020
DOI: 10.1007/s10120-020-01048-6
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-score-matched analysis of a multi-institutional dataset to compare postoperative complications between Billroth I and Roux-en-Y reconstructions after distal gastrectomy

Abstract: Background Few well-controlled studies have compared postoperative complications between Billroth I (B-I) and Rouxen-Y (R-Y). The aim of the present study was to compare the incidence of overall and severe postoperative complications by reconstruction method after distal gastrectomy. Methods We performed a multi-institutional dataset study of patients who underwent distal gastrectomy with B-I or R-Y reconstruction from 2010 to 2014. Using propensity scores to strictly balance the significant variables, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…1,2,6,8,32 However, 2 studies comparing the procedures revealed that RY reconstruction had a significantly higher incidence of DGE, bowel obstruction, internal herniation, and intraabdominal abscess than BI reconstruction. 15,33 Although a previous study has reported a 21% incidence of DGE after RY, 6 it was the most common complication in this study. We diagnosed DGE based on symptoms requiring fasting in patients without gastrointestinal stenosis.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…1,2,6,8,32 However, 2 studies comparing the procedures revealed that RY reconstruction had a significantly higher incidence of DGE, bowel obstruction, internal herniation, and intraabdominal abscess than BI reconstruction. 15,33 Although a previous study has reported a 21% incidence of DGE after RY, 6 it was the most common complication in this study. We diagnosed DGE based on symptoms requiring fasting in patients without gastrointestinal stenosis.…”
Section: Discussionmentioning
confidence: 51%
“…13 Although RY reconstruction can prevent bile reflux, it causes delayed gastric emptying (DGE) or Roux stasis. 6,9,14,15 RY and BI reconstructions had equivalent surgical outcomes and postoperative quality of life in randomized controlled trials and a meta-analysis. 2,16,17 However, reflux esophagitis and remnant gastritis occur more frequently in BI than in RY reconstruction.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In 2019, a RCT study conducted by Ren and Wang 21 showed that the postoperative complications of Billroth I anastomosis were Effects of different gastrointestinal reconstruction techniques on nutrition, anemia, and quality of life in laparoscopic distal gastrectomy for gastric cancer higher than Roux-en-Y anastomosis in laparoscopic radical gastrectomy for gastric cancer. On the contrary, Nakanishi et al 22 conducted a control study on 1,014 patients with distal gastric cancer in 2020 and found that the incidence of postoperative complications of Billroth I anastomosis was lower than that of Roux-en-Y anastomosis. Overall, the incidence of reflux esophagitis in patients with Billroth I anastomosis after distal gastrectomy is higher than that in patients with Roux-en-Y anastomosis 5,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several procedures or methods have been used to improve the nutritional status of patients after a gastrectomy, such as the modification of reconstructive methods, increasing the volume of the remnant stomach, supplemental parenteral nutrition, changes in dietary menus or dietary habits, and recommendations for dietary education [9]. Various reconstructive methods, including increasing the volume of the remnant stomach, have not shown substantial benefits in nutritional parameters over those caused by other procedures [9][10][11][12]. Oral nutritional supplementation (ONS) was not effective in improving nutritional status after a gastrectomy [13].…”
Section: Introductionmentioning
confidence: 99%